PENGARUH CITRA MEREK, KEPUASAN PELANGGAN, KEPERCAYAAN DAN LOVEMARKS DALAM PEMBENTUKAN LOYALITAS MEREK (STUDI KASUS PADA KEDAI KOPI “JANJI JI WA”) - Lolita Ayu Mirosa; Diana Fajarwati (Nusantara Hasana Journal, 2023)
Branding can mean a standardized level of quality so that satisfied consumers will repurchase the product. A coffee shop with a brand that is able to highlight a certain image is used to image its products to consumers and is an important factor in determining and increasing trust that has value in the brand. This study aims to determine the effect of brand image, consumer satisfaction, trust, and lovemarks on the formation of brand loyalty in the Janji Jiwa coffee brand. Sampling in this study were as many as 175 respondents were taken using purposive sampling technique with the respondents' criteria, consumers who were at least 17 years old, who had made at least two purchases and consumed Janji Jiwa coffee products. Data were collected using a questionnaire of 35 questions. The data analysis technique used by researchers in this study is PLS-SEM. The results of this study indicate that four of the seven proposed hypotheses are accepted (H1, H2, H3, H4), while the other three hypotheses cannot be accepted. Hypothesis testing shows that brand image has a positive influence on consumer satisfaction and trust, which if the better the brand image of the Janji Jiwa coffee shop, the brand has succeeded in building and increasing satisfaction and trust in its consumers.